Neo-Babylonian Rock-cut Monuments and Ritual Performance - Da Riva, Rocío (Hebrew bible and ancient Israel, 2018)
The aim of this paper is to review the evidence of the Brisa inscriptions of Nebuchadnezzar II from a new perspective, stressing the ritual aspects of the engagement between monument and landscape, in order to gain insights in the process and circumstances of monument production. As argued elsewhere, the inscriptions are expressions of political power and function as markers of territorial dominion and statements of imperial control. War, religion and politics are clearly intertwined in these iconographic representations and in the texts associated with them. My argument here is that ritual performance played a crucial role in the production and experience of these monuments. I propose the hypothesis that the dual inscriptions and reliefs we find today in the Wadi ash-Sharbin are material traces of a ritual performance gone awry.